Inventarisasi Jamur Di Kawasan Hutan Sekipan Desa Kalisoro Tawangmangu Karanganyar Provinsi Jawa Tengah - Fitriani, Elvira; , Efri Roziaty, S.Si, M.Si (2017)
Sekipan forest at the foot of Mount Lawu, located in Karanganyar, Central Java. Geographically located at coordinates 07039'51.6 "LS and 111011'29.7" longitude, altitude of 1100 m above sea level to 1600 m above sea level, with an area of 4700 Ha. Sekipan forests have high diversity of plant species are small but have a high density because of climatic factors in the area. This condition causes the environment in the area moist and humid, so it is suitable for fungal growth. The purpose of this study to determine the type of fungus in the forest area Sekipan Kalisoro Tawangmangu village in Central Java province. The sampling technique usedmethod Purposive Random Sampling along the ascent of Mount Lawu. Inventory research got 12 family includes 15 species that Laccaria laccata, Coprinus niveus, Heterobasidion irregulare, Heterobasidion sp., Marasmius siccus, Ganoderma applanatum, Ganoderma lucidum, Auricularia auricula, Russula paludosa, Cordyceps ophioglossoides, Hymenochaete tabacina, Cuphophyllus pratensis, Trametes pubescens , Trametes gibbosa, Fomitopsi pinicola.